Some Remarks about Spelling of Local Names in Poland in the Lithuanian language - Davlevič, Miroslav (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English] The purpose of this elaboration is to discuss the matter of spelling of Polish local proper names in the Lithuanian language. The Lithuanian equivalent in Polish terrain names for the most part has already been standardized and published in official lists by the State Commission of the Lithuanian language (Lt. Valstybinė lietuvių kalbos komisija). However, they are not duly disseminated yet for the standardization work has only strengthened in recent years. My observations lead to the conclusion that it is a difficult task to standardize the spelling of proper names. Perhaps, in the future, it would be worth setting up a special commission, like the Commission of the standardization of the geographical names outside Poland (Pol. Komisja Standaryzacji Nazw Geograficznych poza Granicami Rzeczypospolitej Polskiej) that is responsible for determining the Polish geographical names of the world (exonyms). This commission would be responsible for reviewing proposals on the establishment of the original tone and spelling of the names of the geographic objects situated outside the borders of Lithuania, while exonyms established by this commission would be the only valid form of geographic object names beyond the borders of Lithuania recommended for general usage.